Heavy metal contents in registered dietary supplements in Malaysia: a pilot study from the drug safety perspective - Siddiqui, Mohammad Jamshed Ahmad; Ismail, Zahari; Khari, N. S.; Mohamad, N. N.; Jamshed, Shazia Qasim (Elsevier, 2012)
Objectives: In Malaysia dietary supplements are ram- pantly consumed for general health and well-being and therefore, available in community pharmacies, health food stores, night markets, grocery stores and even obtained via internet. However, gap in the level of Malaysian consumer’s awareness regarding the toxicity of dietary supplements is a major issue, which needs to be addressed by the analysis of their constituents. This study was aimed to evaluate and analyze the heavy metal contents such as lead (Pb), cadmium (Cd), arsenic (As) and mercury (Hg) in registered dietary supplements available in community pharmacies in Malaysia Methods: This study was focused on Eurycoma longifolia (Tongkat Ali), glucosamine, Allium sativum (garlic) and Zingiber officinale (ginger) products. A total of twenty registered single ingredient dosage form dietary supple- ments from different brands were purchased from com- munity pharmacies located in Penang. The samples were then evaluated and subjected to analysis by atomic absorption spectrometry. Results: The study showed that variable amounts of lead have been quantified as 0.29 -0.47 ppm (Tongkat Ali), 0.19 – 0.27 ppm (glucosamine), 0.01 – 0.38 ppm (garlic) and 0.26 – 0.74 ppm (ginger) products. While for cad- mium detection, the amounts indicated 0.02 – 0.24 ppm (Tongkat Ali), 0.03 – 0.22 ppm (glucosamine), 0.06 ppm (ginger) and was absent in garlic No traces of arsenic and mercury were found in all four product samples. The regression linear coefficients (r2) for Pb, Cd, As and Hg standards were 0.9990, 0.9958, 0.9960 and 0.9989, respectively. Conclusions: The amount of Pb, Cd, As and Hg in all the products were found within the limits as per the re- quirement stated by National Pharmaceutical Control Bureau (NPCB). Thus, in order to ensure the safety and quality of dietary supplements, the analysis of heavy metals must be carried out on routine basis using simple and robust atomic absorption spectrometry (AAS) technique